Improving our understanding of the disproportionate incidence of STIs in heterosexual-identifying people of black Caribbean heritage: findings from a longitudinal study of sexual health clinic attendees in England. (29th January 2021) - Bardsley, Megan; Wayal, Sonali; Blomquist, Paula; Mohammed, Hamish; Mercer, Catherine H; Hughes, Gwenda
Abstract : Objective: In England, people of black minority ethnicities are at elevated risk of STI diagnosis, especially those of black Caribbean (BC) heritage. Understanding the factors that predict STI acquisition in this population is key to inform prevention measures. We examined the differences in predictors of incident STI diagnoses across ethnic groups in people attending sexual health clinics (SHCs). Methods: Responses from an attitudinal and behavioural survey run in 16 English SHCs (May–September 2016) were linked to routinely collected national surveillance data on bacterial STI or trichomoniasis diagnoses. Cox proportional hazards models investigated the relationship between participant characteristics and rate of incident STI in the 18 months after survey completion for all heterosexual participants (N=2940) and separately for heterosexual BC (N=484) and white British/Irish (WBI, N=1052) participants. Results: We observed an overall STI incidence of 5.7 per 100 person-years (95% CI 5.1 to 6.5). STI incidence was higher in participants of BC ethnicity (BC, 12.1 per 100 person-years, 95% CI 9.7 to 15.1; WBI, 3.2 per 100 person-years, 95% CI 2.4 to 4.2), even in adjusted analysis (BC adjusted HR (aHR), 2.60, p<0.001, compared with WBI). In models stratified by ethnicity, having had two or more previous STI episodes in the past year was the strongest predictor of incident STI for both BC (aHR 5.81, p<0.001, compared with no previous episodes) and WBI (aHR 29.9, p<0.001) participants. Aside from younger age (aHR 0.96 for increasing age in years, p=0.04), we found no unique predictors of incident STI for BC participants. Conclusions: Incident STI diagnoses among SHC attendees in England were considerably higher in study participants of BC ethnicity, but we found no unique clinical, attitudinal or behavioural predictors explaining the disproportionate risk. STI prevention efforts for people of BC ethnicity should be intensified and should include tailored public health messaging to address sexual health inequalities in this underserved population.